Raman spectroscopy of GeSe and AgGeSe thin films - Conde Garrido, Juan Manuel (2013)
The structural properties of Agy(Ge0.25Se0.75)1-y thin films (y=0, 0.07, 0.10, 0.15, 0.20 and 0.25 at. fraction) were studied. The films were prepared by pulsed laser deposition using bulk glass targets of the studied ternary system and deposited onto microscope slides. Their amorphous structures were confirmed by XRD (X-ray Diffraction). The effect of silver content on films structures was analysed by Raman spectroscopy. Typical Raman vibration modes were observed in the Ge0.25Se0.75 binary film: Ge-Se corner-sharing tetrahedra mode (CS) at 199 cm-1, edge sharing tetrahedra mode (ES) at 217 cm-1, and SeSe rings and chains mode at 255-265 cm-1 (CM). In the Agy(Ge0.25Se0.75)1-y ternary thin films, the same modes were observed but with a red shift and an intensity reduction in the ES and CM bands.